Using Social Media Mining to Understand Public Opinion towards Destination Image - Budi, Tomas Setya Wahyu; Wen, Shen Chien; Ratnawati, Kusuma (Department of Management, Faculty of Economics and Business, Brawijaya University, 2017)
In the middle of highly competitive tourism market, development of successful destination image is paramount towards memorable experience for visitors. This study aims to support tourism stakeholders from the service providers and national tourism by analyzing, and extracting meaningful patterns from social media, e.g. Twitter, based on destination image information. This data plays an important role for destination marketers to distinguish their destination among others based on Twitter Statistics and key public opinion towards destination image attributes. London and New York were used as destination cities under the analysis of text mining with the concept linkage approach. Results shows five distinct keywords attributed to each city. Each keyword found to be relevant in representing the image of destination cities based on the public opinion on Twitter. For keyword â€œCulture and Culturalâ€, term